Ādivāsi jīvitaṃ, oru sāṃskārika paṭhanaṃ : paṭhanaṃ - Dirār, Vi. Ecc. (Ayyanthole, Thrissur : Gr̲īn Buks, 2016)
On Adivasis in Kerala, India.
In Malayalam.
Keywords: Indigenous peoples; India -- Kerala